Determinan Mempengaruhi Kebijakan Hutang Perusahaan Sub Sektor Makanan dan Minuman di Bursa Efek Indonesia - Wardah Diya Khumaira; Amrizal Amrizal; Masriyanda Masriyanda; Yofnedi Yofnedi; Sri Setia Ningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The aim of this research is to prove the influence of free cash flow, asset structure and sales growth on debt policy partially and simultaneously. The research design uses quantitative descriptive, the research variables consist of three independent variables, namely the free cash flow variable, asset structure variable, and sales growth while the dependent variable is debt policy. The research data is secondary data consisting of financial reports of food and beverage sub-sector companies from 2019 to 2022 which are listed on the Indonesian stock exchange. The sample collection technique uses purposive sampling technique. The research uses multiple linear regression analysis. The research results prove thatvariable The variable Variable Based on the results of the F test, the significance value is 0.000<0.05 and the calculated F is greater than F table 18.725>2.712, meaning that simultaneously free cash flow, asset structure and sales growth have a significant effect on debt policy. The magnitude of the influence of the three Independent variabel is 40.1%.